Multiple Resistance to PS II-Inhibiting and ALS-Inhibiting Herbicides in Common Lambsquarters (Chenopodium album L.) from China - Jinglin Li; Lichun Huang; Yue Li; Ruolin Wang; Shenao Hu; Zhaofeng Huang (Agronomy, 2025)
Chenopodium album is a troublesome weed in soybean fields in China. Many C. album populations have evolved resistance to herbicides and pose a growing challenge to weed management. This study characterizes the molecular and physiological resistance mechanisms in C. album populations against ALS- and PSII-inhibiting herbicides, focusing on thifensulfuron-methyl and bentazone. Dose-response assays confirmed significant resistance in two populations (R1 and R2), with resistance index values of 5.28 and 6.51 for thifensulfuron-methyl, and 4.83 and 5.10 for bentazone. Herbicide target gene amplification and sequence analysis showed an Ala-122-Thr substitution in the ALS but no psbA mutation in R1, while no ALS or psbA mutation was identified in R2. ALS enzyme assays further supported the resistance in R1. Cross-resistance tests indicated that R1 and R2 populations exhibited low-level resistance to oxyfluorfen and acifluorfen, but no detectable resistance to cloransulam-methyl, flumetsulam, or fomesafen. These findings highlight the need for integrated weed management strategies, including herbicide diversification and metabolic resistance monitoring, to mitigate the further evolution of resistance.